Artificial intelligence in healthcare system - Roncea, Florentina-Nicoleta; Cazacincu, Radu-George; Mireșan, Horațiu; Roșca, Adrian-Cosmin; Erimia, Cristina-Luiza (Technium BioChemMed, 2023)
Artificial intelligence (A.I.) represents various intelligent processes and behaviors, developed by computational models, algorithms or a set of rules that support the machine to imitate the cognitive functions of humans, such as learning, problem solving. AI technologies in healthcare include machine learning (ML), natural language processing (NLP), physical robots, robotic process automation. Regulators should collaborate with existing networks of ethics committees and AI expert groups on the ethical issues of AI in the development, use and regulation of human medicines, promoting collaboration between drug and medical device regulatory authorities to harmonize views, needs and requirements.